Anatomical variation of the extensor tendons of the second toe in the dorsum of the foot: a case report. - Sirasanagandla, SR; Satheesha, BN; Kumar, MR Bhat; Swamy, RS; Deepthinath, R (Department of Surgery, UKM Medical Centre, 2013)
Extension of the lateral four toes of the foot is caused by the extensor digitorum longus. Each tendon of the extensor digitorum longus is attached to the middle and distal phalanges of the corresponding toes. The medial three tendons receive the insertion of lateral three tendons of the extensor digitorum brevis. During regular dissection for the undergraduate medical students, we came across a rare variation of extensor tendons of the second toe. The extensor digitorum brevis gave two tendinous slips to the second toe; medial slip and lateral slip. The extensor digitorum longus tendon for the second toe received the insertion of extensor digitorum brevis medial slip for the second toe, opposite to the base of second metatarsal bone. Further, the lateral slip of the extensor digitorum brevis was inserted to the lateral side of the extensor digitorum longus tendon for the second toe, opposite to the base of the proximal phalanx. Precise knowledge about the anomalies of extensors of the toes is clinically important while harvesting the tendon grafts. The knowledge of the anomaly presented in present case report is also important during plastic and orthopaedic surgeries as preference and selection of a donor site for a tendon graft is crucial.